Effects of Endosymbionts on the Nutritional Physiology and Biological Characteristics of Whitefly Bemisia tabaci - Han Gao; Xiang-Jie Yin; Zhen-Huai Fan; Xiao-Hang Gu; Zheng-Qin Su; Bing-Rui Luo; Bao-Li Qiu; Li-He Zhang (Insects, 2025)
Insects and their endosymbionts have a close mutualistic relationship. However, the precise nature of the bacterial endosymbiont-mediated interaction between host plants and whitefly Bemisia tabaci MEAM1 is still unclear. In the present study, six populations of Bemisia tabaci MEAM1 sharing the same genetic background were established by rearing insects for ten generations on different host plants, including poinsettia, cabbage, cotton, tomato, and tobacco, and an additional population was reared on cotton and treated with antibiotics. The physiological and nutritional traits of the insects were found to be dependent on the host plant on which they had been reared. Systematic analysis was conducted on the endosymbiont titers, the amino acid molecules and contents, as well as developmental and oviposition changes in the MEAM1 populations reared on each host plant tested. The results indicate that B. tabaci contained the primary symbiont Portiera and the secondary symbionts Hamiltonella and Rickettsia. In addition, the titer of endosymbiotic bacteria in females is higher than that in males. Among the MEAM1 populations reared on each host plant, the variation pattern of Portiera titer generally corresponded with changes in biological characteristics (body length, weight and fecundity) and AA contents. This suggests that changes in the amino acid contents and biological characteristics of different B. tabaci populations may be due to changes in the Portiera content and the differences in the nutrition of the host plants themselves. Our findings were further confirmed by the reduction in Portiera with antibiotic treatment. The amino acids, body size, body weight, and fecundity of B. tabaci were all reduced with the decrease in the Portiera titer after antibiotic treatment. In summary, our research revealed that host plants can affect the content of symbiotic bacteria, particularly Portiera, and subsequently affect the nutrition (i.e., the essential amino acids content) of host insects, thus changing their biological characteristics.